Single-center experience of venetoclax combined with azacitidine in young patients with newly diagnosed acute myeloid leukemia - Xuezhu Xu; Rui Liu; Hongli Chen; Ruoyu Yang; Gongzhizi Gao; Aili He; Fangxia Wang (Therapeutic Advances in Hematology)
Background: Medical resources, especially blood products, were in short supply during the COVID-19. Less intensive therapy with hypomethylating agents/venetoclax (VEN) seems an effective treatment option for patients with acute myeloid leukemia (AML). Objectives: To retrospectively analyze the efficacy and safety of VEN combined with azacitidine (AZA) in young adult patients with newly diagnosed (ND) AML. Design: This was a retrospective study. Methods: The clinical data of 25 AML patients treated with the VEN + AZA regimen from January 2021 to December 2023 at our center were collected, compared with a randomized historical study cohort that was administered intensive chemotherapy (IC) from January 2018 to December 2019. Results: No rate of complete remission/complete remission with incomplete count recovery differences observed between the two arms reached statistical significance. Compared to traditional IC, minimal residual disease (MRD)-negative remission was achieved more quickly in patients treated with VEN + AZA regimens (after cycle 1: 8% in the IC group vs 56% in the VEN group, p = 0.0004; after cycle 2: 16% in the IC group vs 72% in the VEN group, p = 0.0001), especially in those AML patients who had a poor prognosis. The dependency of transfusion of red blood cell (RBC) and platelets during induction treatment was significantly lower in the VEN + AZA group (RBC: p = 0.0269; platelet: p = 0.0054). Compared with the standard IC, the incidence rate of non-hematological adverse events in VEN + AZA group was significantly decreased (infection: 100% vs 20%, p = 0.0001; gastrointestinal side effects: 48% vs 12%, p = 0.0055). The total hospitalization cost of the VEN group was significantly less than that of the IC group ( p = 0.0395). Conclusion: In conclusion, our study indicated that VEN + AZA with a higher MRD-negative remission rate and less toxic appeared to be a therapy option for young patients with ND AML. However, further well-designed studies with larger numbers of patients are needed to confirm the benefits of VEN + AZA in this population.